The Uniqueness of STAD and CIRC Models in Poetry Learning (Keunikan Model STAD dan CIRC dalam Pembelajaran Puisi) - Diyan Permata Yanda; Dina Ramadhanti (Jurusan Tadris Bahasa Indonesia, 2021)
The purpose of this study is to describe the uniqueness of the Student Team Achievement Division (STAD) and Cooperative Integrated Reading and Composition (CIRC) models in terms of poetry learning. This is a quantitative study that uses a pure experimental method. The randomized posttest in the control group was used as the experimental design. With the average similarity test, the study sample was chosen randomly, class of Experiment I and Experiment II. The STAD model was used to teach poetry to experimental class I, and the CIRC model was used to teach poetry to experimental class II. Both learning models can be employed in poetry learning, according to the findings, because they improve poetry understanding skills, social skills in terms of interpreting poetry content, and the process and ultimate outcomes of poetry learning. Both types have their own distinct characteristics that make them suited for poetry instruction. The STAD model differs from others in that it creates opportunities for students to collaborate in groups, take responsibility, and high abilities. The CIRC model is unique in that it divides students into groups according to their level of reading interest, collaborate and encourage one another.Penelitian ini bertujuan untuk mendeskripsikan keunikan Model STAD (Student Team Achievement Division) dan CIRC (Cooperative Integrated Reading and Composition) dalam pembelajaran puisi.Â Jenis penelitian ini adalah kuantitatif dengan metode eksperimen murni. Desain eksperimen yang digunakan adalah the randomized posttest only control group design. Sampel penelitian dipilih secara random dengan uji kesamaan rata-rata, yakni kelas Eksperimen I dan Eksperimen II. Kelas eksperimen I menerima pengajaran puisi dengan model STAD dan kelas eksperimen II menerima pengajaran puisi dengan model CIRC. Hasil penelitian menunjukkan bahwa kedua model pembelajaran dapat digunakan dalam pembelajaran puisi karena memberi dampak pada peningkatan keterampilan memahami puisi, peningkatan kemampuan sosial dalam hal memaknai isi puisi, dan peningkatan proses dan hasil belajar puisi secara keseluruhan. Keunikan model STAD adalah pemberian reward yang memberikan dorongan kepada mahasiswa untuk berkolaborasi kelompok, bertanggung, dan pendampingan agar kemampuan kelompok merata. Keunikan model CIRC adalah pembagian kelompok yang didasarkan pada tinggi rendahnya minat baca mahasiswa, bekerja sama, dan saling memotivasi.